Plasma immersion ion implantation (PIII) influence on Ti-6Al-4V alloy: Frequency effect. (April 2018) - Oliveira, V.M.C.A.; Cioffi, M.O.H.; Barboza, M.J.R.; Landers, R.; Schmitt, B.; Tapia, D.C.A.R.; Voorwald, H.J.C.
Highlights: Experimental results showed an influence of PIII on fatigue strength of Ti6Al4V. Frequency parameter effect presented the major influence on the S vs N curves. When f  = 1000 Hz, the roughness played an important role on the fatigue strength. For f  = 1500 Hz, there is a competition between roughness and crack nucleation. For f  = 1200 Hz, TiN and Ti2 N formation on surface is responsible for fatigue life. Abstract: The plasma immersion ion implantation treatment (PIII) acts to increase mechanical resistance with solid solution formation, new phases and defects inclusion, besides chemical and residual stress profile modification. Ti-6Al-4V alloy presents poor tribological properties and high affinity with interstitial elements, such as nitrogen and oxygen, this makes it more reactive at high temperatures. This paper aims to study Ti-6Al-4V alloy fatigue behavior subjected to nitrogen addition by plasma immersion ion implantation. It was investigated the frequency parameter influence on fatigue resistance. Ti-6Al-4V alloy was PIII treated with voltage equal to 9.5 kV, frequencies varying between 1000 and 1500 Hz and submitted to axial fatigue tests. Axial fatigue tests were performed, at room temperature and R = 0.1. Ti-6Al-4V alloy fatigue results were supported by Weibull statistics analysis. Ti-6Al-4V alloy microstructural analysis showed equiaxed α + β grains. Weibull analysis at untreated condition presented m values greater than 1, indicating reliability and uniformity. For a lifetime of 10 7 cycles, fatigue resistance was equal to 829 MPa for untreated condition, 644, 767 and 417 MPa, for f  = 1000, 1200 and 1500 Hz, respectively. The nitrogen-based compounds were detected only at the condition where f  = 1200 Hz. Thus, the combination of PIII treatment parameters, when f  = 1200 Hz, hindered crack nucleation and increasing fatigue resistance of treated Ti-6Al-4V alloy when compared with the other two treatment conditions.